Modeling dan Simulasi Finite Element Analysis pada Segitiga T Sepeda Motor Menggunakan Sofware Ansys 2023 - Iqbal Dumyati; Soffan Nurhaji (Quantum Teknika : Jurnal Teknik Mesin Terapan, 2023)
This study used finite element analysis method to analyze the underbracket T triangle on motorcycles using ANSYS 2023 R1 software. The material used is Structural Steel. The simulation is done by accurately modeling the triangle and meshing using the default algorithm. The boundary conditions are set by providing fixed support at all four-hole points and providing a load of 1000N on the Y-axis. The simulation results show a maximum equivalent stress (Von-Mises stress) of 7.173 MPa, which is still below the strength limit of the material. The underbracket T-triangle undergoes a maximum deformation of 0.00063309 mm at the upper right fork hole. This deformation indicates the extent to which the triangle changes shape due to the load applied. The safety factor obtained is greater than 1, indicating that the triangle has adequate safety to withstand the load. With a better understanding of the structural behavior of the underbracket triangle, the design can be improved to improve the strength and performance of the motorcycle.